Comparison of higher order wavefront aberrations with four aberrometers - Cook, William H (Indian J Ophthalmol, 2019)
PURPOSE: To evaluate the agreement of selected higher order aberration measurements between aberrometers based on three different wavefront technologies. METHODS: Twenty-three eyes of 23 participants were compared between Zywave, OPD-Scan III, and iDesign aberrometers, for total ocular aberrations. Participants were between 19 and 69 years of age, and exclusion criteria were previous ocular surgery or trauma, contact lens wear within the preceding 2 weeks, and ocular or systemic disease. Corneal aberrations were compared between the OPD-Scan III and GALILEI™ G2 aberrometers. Zernike coefficients of vertical and oblique trefoil, vertical and horizontal coma, and spherical aberration were analyzed in R software. RESULTS: In all, 276 scans were captured in total, with a male-to-female ratio of 11:12. Total ocular vertical coma [mean difference (MD) = 0.026 μm, P < 0.005], vertical trefoil (MD = 0.033 μm, P < 0.05), and spherical aberration (MD = 0.022 μm, P < 0.05) differed significantly between the iDesign and OPD-Scan III. Differences in total vertical (MD = 0.072 μm, P < 0.05) and oblique trefoil (MD = 0.058 μm, P < 0.05) were demonstrated between the Zywave and OPD-Scan III, and spherical aberration (MD = 0.030 μm, P < 0.005) between iDesign and Zywave. iDesign corneal horizontal coma (MD = 0.025 μm, P < 0.05) and spherical aberration (MD = 0.043 μm, P < 0.005) measurements were significantly different between the GALILEI™ G2 and the OPD-Scan III. CONCLUSION: Zywave, iDesign, and OPD-Scan III, and GALILEI™ G2 and OPD-Scan III may be used interchangeably for their total ocular and corneal wavefront functions, respectively; however, care must be taken if using these devices for guiding ablation or monitoring corneal disease.